Perception of car workshop partners towards the vocational students’ internship performance in Cilacap - Eka Rini Widiastuti; Budi Santosa; Muhammad Sayuti (Universitas Ahmad Dahlan, 2021)
This research aims to determine the perceptions of industrial partners of the car workshop on the performance of vocational high school students in Cilacap after conducting internship program. The type of this research is descriptive qualitative. The data collection techniques used questionnaires. To test the validity and research data, we used triangulation of data that is how researchers test the validity of data by collecting similar data but by using different data collection techniques. The data to be concluded is about the performance of internship students. The performance of internship students is concluded with different methods, namely the questionnaire method and the interview method.